Pengaruh Return On Asset (Roa) Dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan Pada Perusahaan Pertambanganbatubara Yang Terdaftar Di Bursa Efek Indonesia - Rezki Zurriah (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study aims to determine the effect of Return On Assets (ROA) and sales growth on firm value in coal mining companies listed on the Indonesia Stock Exchange. This research is a type of associative research. The sampling technique was carried out using a purposive sampling technique. So that the sample obtained is 14 coal mining companies listed on the Indonesia Stock Exchange in 2015 - 2019 with a total of 70 observational data for 5 years of observation. The data collection technique used is documentation with data sources using secondary data taken through the official website of the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear regression analysis with SPSS 26 software tools. The results of this study indicate that Return on Assets (ROA) has an effect and is significant on firm value. Sales growth has no effect and is not significant to firm value. Then Return On Assets (ROA) and sales growth affect the firm value simultaneously.